Optimalisasi Sistem Pemeliharaan Gedung Sekolah Berbasis Partisipasi Masyarakat (Studi Kasus: SDN 16 Meulaboh) - Edi Mawardi; Bambang Tripoli; Samsunan Samsunan; Herza Zifra (Fakultas Teknik, 2021)
School building infrastructure needs maintenance and thi is not only carried out by the government but also involve community. The purpose of this study was to determine the existing condition of the school building and the efforts of community participation in building maintenance. This research was conducted at the SD 16 Meulaboh. Methods of data collection by field observations, interviews and distributing questionnaires to the school community (the community around the school, students, teachers, and school administrators). Data processing used a Likert scale, then classifying it into three categories, the first is the low with a score below 46, the medium scores between 46 - 76, and the high is more than 76. Meanwhile, the results of interviews and observations were analyzed using descriptive methods. The results of the study on the existing condition of the school building in a slightly damaged condition where the damage occurred only to non-structural components, namely floor coverings, infill walls, as well as doors and windows. The results were divided into two groups, namely residents and students, citizen participation in the medium category reached 7 people (12.07%) while high participation reached 51 people (87.93%). Student participation in the medium category reached 4 people (10.00%), while high participation reached 36 people (90.00%). This shows that the community of SD Negeri 16 Meulaboh has a high participation in the routine maintenance of the school building.